Demographic Characteristic Of Patient With Traumatic Dental Injury Attending Kulliyyah Of Dentistry IIUM Kuantan Campus - Ismail, Ahmad Faisal; Ghazali, Aifaa; Abdullah, Afiza Fatihah; Mat Daud, Muhamad Sharifuddin (IIUM Medical Journal Malaysia, 2017)
Introduction: Traumatic dental injuries (TDI) refer to injury to the teeth and/or peridontium and perioral soft tissues. To date, very few dental trauma studies conducted in the university setting, thus the aim of this research is to provide an epidemiological data of TDI cases among patients attending Kulliyyah of Dentistry (KOD), IIUM Kuantan Campus. Materials and Methods: A total of 32 patient's record with TDI were retrieved from 2012 to June 2016. The inclusion criteria are patients attended KOD for management of dental trauma and diagnosis of TDI was properly documented. Patients attending KOD with complaint other than dental trauma and no proper diagnosis documented were excluded. The classification of dental trauma used is based on WHO Dental Trauma Classification (1978). For cases that were doubtful or with insufficient information, decision was made after further discussion with another examiner. Results: The mean age was 12.31 years old with the highest number of cases occurs in the 6-15 year-old group (37.5%) and male to female ratio of 3:2. Uncomplicated crown fracture was the most common injury in primary and permanent dentition (38% and 67%, respectively). Falls attribute 62.5% of the causes of TDI. November and December recorded the highest number of occurance of TDI cases (25% respectively). Conclusion(s): There is low occurance of TDI cases in KOD. The occurance of TDI cases is associated with school holiday